SCO Forum: facing the enlargement - A. Bykov; O. Puzanova (Международная аналитика, 2017)
The Shanghai Cooperation Organization is on the verge of a new transformation into a more influential international organization, which is why the SCO Forum held in Tashkent this year has become one of the most r epresentative of the recent years. The forum has been held regularly since 2006 and always brought together leading experts from the member countries of the organization. Due to the arrangements made by the Institute for Strategic and Interregional Studies under the President of the Republic of Uzbekistan, this year the member countries and observer countries took part in productive discussions on such important matters as stability and security in the region, as well as discussed prospects for expanding the organization concluding that the process should not dilute the fundamental principles of the Organization’s activities.Experts have also agreed that bilateral contradictions between individual member countries should not hamper the achievement of general agreement and development of consensual decisions on key issues on the SCO agenda. The ‘Shanghai spirit’ enshrined in the Charter and based on the principles of mutual trust, benefit, equality, and prevention of any unlawful actions directed against the interests of other member states, should become an ethical code that emphasizes the high level of partnership and trust within the SCO framework. The inclusion of India and Pakistan in the SCO bears a special significance. Such enlargement will give the organization a completely different meaning, as well as lay out new tasks for member countries and open prospects for a new format of multilateral relations based on mutual consideration of interests within the institutional framework of the Organisation.